sud1(+) targets cyclin-dependent kinase-phosphorylated Cdc18 and Rum1 proteins for degradation and stops unwanted diploidization in fission yeast - Jallepalli, Prasad V. (The National Academy of Sciences, 1998)
In the fission yeast Schizosaccharomyces pombe, S phase is limited to a single round per cell cycle through cyclin-dependent kinase phosphorylation of critical replication factors, including the Cdc18 replication initiator protein. Because defects in Cdc18 phosphorylation lead to a hyperstable and hyperactive form of Cdc18 that promotes high levels of overreplication in vivo, we wished to identify the components of the Cdc18 proteolysis pathway in fission yeast. In this paper we describe one such component, encoded by the sud1(+) gene. sud1(+) shares homology with the budding yeast CDC4 gene and is required to prevent spontaneous re-replication in fission yeast. Cells lacking sud1(+) accumulate high levels of Cdc18 and the CDK inhibitor Rum1, because they cannot degrade these two key cell cycle regulators. Through genetic analysis we show that hyperaccumulation of Rum1 contributes to re-replication in Δsud1 cells, but is not the cause of the defect in Cdc18 proteolysis. Rather, Sud1 itself is associated with the ubiquitin pathway in fission yeast and binds to Cdc18 in vivo. Most importantly, Sud1-Cdc18 binding requires prior phosphorylation of the Cdc18 polypeptide at CDK consensus sites. These results provide a biochemical mechanism for the phosphorylation-dependent degradation of Cdc18 and other cell cycle regulators, including Rum1. Evolutionary conservation of the Sud1/CDC4 pathway suggests that phosphorylation-coupled proteolysis may be a general feature of nearly all eukaryotic cell cycles.